MUC3A promotes the progression of cholangiocarcinoma through the MAPK/ERK pathway - Baijie Feng; Wei Su; Lina Hu; Minghua Yu (Discover Oncology)
Abstract Aim Cholangiocarcinoma (CCA) is the most common malignant tumor of the bile ducts. Due to its anatomical location, growth pattern, and lack of clear diagnostic criteria, it presents diagnostic challenges. Exploring its occurrence and development to find early markers and treatment targets is of great significance. Methods To determine whether Mucin 3A (MUC3A) can regulate the occurrence and development of cholangiocarcinoma cells and its mechanism, we compared the expression levels of MUC3A between intrahepatic biliary epithelial cells and cholangiocarcinoma cells and constructed stable transfections of KONC (transfection negative control group) and MUC3A-KO1 and KO2 (transfection MUC3A knockout vectors) lentivirus in CCA cell lines. We investigated the effect of MUC3A on the proliferative capacity of cholangiocarcinoma cells using the CCK-8 assay and colony formation assay. The regulatory effect of MUC3A on the cell cycle of cholangiocarcinoma cells was examined using flow cytometry. The impact of MUC3A on the invasion and migration of cholangiocarcinoma cells was observed through scratch and Transwell assays. Additionally, the mechanism by which MUC3A regulates proliferation and metastasis of cholangiocarcinoma was explored using Western blot. Results MUC3A is highly expressed in cholangiocarcinoma. MUC3A promotes the proliferation of cholangiocarcinoma cells by regulating the cell cycle. Additionally, MUC3A enhances the invasion and migration of cholangiocarcinoma cells by regulating the epithelial-mesenchymal transition. Furthermore, MUC3A regulates the proliferation and metastasis of cholangiocarcinoma cells through the ERK signaling pathway. Conclusions This study demonstrates that MUC3A regulates the proliferation and metastasis of cholangiocarcinoma cells through the ERK signaling pathway.